2017
DOI: 10.1111/gcb.13853
|View full text |Cite
|
Sign up to set email alerts
|

Peaks of in situ N2O emissions are influenced by N2O‐producing and reducing microbial communities across arable soils

Abstract: Agriculture is the main source of terrestrial N 2 O emissions, a potent greenhouse gas and the main cause of ozone depletion. The reduction of N 2 O into N 2 by microorganisms carrying the nitrous oxide reductase gene (nosZ) is the only known biological process eliminating this greenhouse gas. Recent studies showed that a previously unknown clade of N 2 O-reducers (nosZII) was related to the potential capacity of the soil to act as a N 2 O sink. However, little is known about how this group responds to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 75 publications
6
70
3
Order By: Relevance
“…After analysis of more than 59,000 N 2 O field measurements, Domeignoz‐Horta et al. () found that only high emissions rates were explained by variation in abundance and diversity of microbial communities, while rates of N 2 O emissions measured in this study fell at the low end of the observed range.…”
Section: Discussionmentioning
confidence: 48%
“…After analysis of more than 59,000 N 2 O field measurements, Domeignoz‐Horta et al. () found that only high emissions rates were explained by variation in abundance and diversity of microbial communities, while rates of N 2 O emissions measured in this study fell at the low end of the observed range.…”
Section: Discussionmentioning
confidence: 48%
“…availability of O 2 , or carbon). (2018) (van Kessel et al, 2015) or N 2 O reduction (Sanford et al, 2012;Jones et al, 2014;Domeignoz-Horta et al, 2017). Domeignoz-Horta et al (2017) found that N 2 O hotspots were predominantly controlled by changes in the microbial communities, whereas lower N 2 O-producing areas were more likely to be controlled by variation in soil properties.…”
Section: Researchmentioning
confidence: 94%
“…(2018) (van Kessel et al, 2015) or N 2 O reduction (Sanford et al, 2012;Jones et al, 2014;Domeignoz-Horta et al, 2017). Domeignoz-Horta et al (2017) found that N 2 O hotspots were predominantly controlled by changes in the microbial communities, whereas lower N 2 O-producing areas were more likely to be controlled by variation in soil properties. Using similar organic patches as in the present study, Nuccio et al (2013) found that while there was no overall change in bacterial diversity, the presence of AMF hyphae significantly modified the bacterial community.…”
Section: Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…The phylogeny of the nitrous oxide reductase (NosZ), encoded by the nosZ gene, has two major clades, clade I and II (Jones et al ., ). A high abundance and diversity of N 2 O reducing bacteria harboring nosZ clade II, in particular, has been linked to an increased N 2 O reduction potential in soils as well as lower in situ N 2 O emissions (Jones et al ., ; Domeignoz‐Horta et al ., ), but a mechanistic explanation for this is lacking. nosZ clade I and clade II differ in (i) the co‐occurrence with other denitrification genes, with nosZ clade II being more often associated to non‐denitrifiers (Graf et al ., ) and (ii) the accessory proteins associated to the nos operon.…”
Section: Introductionmentioning
confidence: 99%